Yugoslav-Greek relations from the end of the Second World War to 1990 chronology, phases, problems and achievements - Ristović Milan (Balcanica, 2020)
Yugoslav-Greek relations from the end of WWII to the breakup of Yugoslavia and went through several phases. A short period of interlude when the diplomatic relations were re-established 1945/1946 was followed by a much longer one (1946-1950) of conflict due to the Yugoslav support to the Communists in the Greek Civil War. A pragmatic approach to the issue of both parties resulted in a prolonged period (1950-1967) of working relations that culminated in the signing of tripartite treaties with Turkey, Treaty of Ankara (1953) and Bled Agreements (1954). Even though the treaties lost most of their importance after the reconciliation between Belgrade and Moscow in 1955/1956, and the Cyprus crisis, they created a climate of correct relations between two neighbouring states marked by reciprocal visits on the highest level. The coup d’état of April 1967 brought to power a dictatorship in Greece (1967-1974) and thus inaugurated a new period of tensions in bilateral relations. The last period 1974-1990 was characterized by good working relations between Belgrade and Athens mainly due to the Greece’s efforts to integrate the European Economic Community (EEC) that supposed good relations with its neighbours. The issue of relations of Athens with Socialist Republic of Macedonia, first as a part of Socialst Yugoslavia, and then, after the collapse of the Federation, as the independent country, proved to be the last problem for Yugoslavia and a lasting one for the Former Yugoslav Republic of Macedonia, as it used to be known after 1990.